Given the equation:
1 + logx = log(7x + 2)
Let's solve the equation for x.
To solve for x, aply the following steps:
Step 1:
Subtract logx from both sides
1 + logx - logx = log(7x + 2) - logx
1 = log(7x + 2) - logx
logx - log(7x + 2) = -1
Step 2:
Apply the quotient property of logarithms
![\log ((x)/(7x+2))=-1](https://img.qammunity.org/2023/formulas/mathematics/college/tclqxlpck5j1gnp1hcra8mil0297uylwbw.png)
Step 3:
Rewrite log in exponential form
![(x)/(7x+2)=10^(-1)](https://img.qammunity.org/2023/formulas/mathematics/college/mojxfl533a45zfmwa8exr8meb7wjbndn68.png)
Step 4:
Cross multiply
![x=(7x+2)10^(-1)](https://img.qammunity.org/2023/formulas/mathematics/college/91dv6t63s3k1q73pcmjafui0pa37ec47th.png)
Step 5:
Simplify
![\begin{gathered} x=(7x+2)/(10) \\ \\ x=(7x)/(10)+(2)/(10) \\ \\ x=(7x)/(10)+(1)/(5) \\ \\ x-(7x)/(10)=(1)/(5) \\ \\ (10x-7x)/(10)=(1)/(5) \\ \\ (3x)/(10)=(1)/(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y7yy5s0mkj32m6gsosjsd7dk5zvd22veyt.png)
Solving further:
Cross multiply
![\begin{gathered} 3x(5)=10(1) \\ \\ 15x=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kaa1jwzlwyzl3z9xkwhrdskbhw1txa8gks.png)
Divide both sides by 15:
![\begin{gathered} (15x)/(15)=(10)/(15) \\ \\ x=(2)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zc11hlq8ojg8j9n1fwl708zri5e4z40ong.png)
Therefore, the value of x is:
![(2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/zeht2hdwlb899wfchg7j67j4mj43o3xc1c.png)
ANSWER:
![(2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/zeht2hdwlb899wfchg7j67j4mj43o3xc1c.png)